1985
DOI: 10.1126/science.228.4707.1527
|View full text |Cite
|
Sign up to set email alerts
|

Brachiopods versus Mussels: Competition, Predation, and Palatability

Abstract: Unlike other shell-enclosed marine invertebrates, articulate brachiopods are repellent to predators. Fish, sea stars, snails, and crabs all prefer bivalve molluscs such as mussels to articulates. The mussels tested are mobile and out-compete immobile articulates when space is limited. In subtidal field experiments, mussels alone and predators alone each reduced the survivorship of articulates. However, adding mussels to articulates in the presence of ambient predation increased brachiopod survivorship by diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 34 publications
1
78
0
1
Order By: Relevance
“…Such an explanation would parallel the general trend in brachiopod decline during Mesozoic times. Numerous authors (Gould and Calloway 1980;Thayer 1985Thayer , 1986Ager 1986) have suggested that after the P−T crisis brachiopods were outcompeted by bivalves in a majority of environments. Still there are some Recent examples where brachiopods successfully coexist with bivalves (Lee 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such an explanation would parallel the general trend in brachiopod decline during Mesozoic times. Numerous authors (Gould and Calloway 1980;Thayer 1985Thayer , 1986Ager 1986) have suggested that after the P−T crisis brachiopods were outcompeted by bivalves in a majority of environments. Still there are some Recent examples where brachiopods successfully coexist with bivalves (Lee 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As an explanation for abandoning of half−crushed shell of Cyrtiorina sp., Baliński (1993) suggested that the brachiopod developed a skill to emit a repellent. This kind of chemical defence is well known in extant articulate brachiopods (Thayer 1985;Thayer and Allmon 1991), pleurotomarioidean gastropods (Harasewych 2002), and phoronids (Larson and Stachowicz 2009). Recent experiments of Mahon et al (2003) on palatability of soft tis− sue of terebratulid Liothyrella uva (Broderip, 1833) from Antarctica show that the brachiopod is unpalatable to the sympatric macropredators, such as omnivorous sea stars and epibenthic fish.…”
Section: Shell Damagementioning
confidence: 99%
“…This is a form of coevolution [1,29]. In addition to this predator-prey interaction, brachiopod survival on the sea bottom is also affected by competition among benthic organisms, which belong to a similar guild [30][31][32]. As a consequence, several species of the benthic community are involved, and their abundances are not independent.…”
Section: One Likely Possibility For the Evolutionary Arms Race Betweementioning
confidence: 99%